On a programme for the balancing calculation of flexible rotors with the influence coefficient method - Khang, Nguyen Van; Luong, Tran Van (Vietnam Journal of Mechanics, 2000)
This paper presents the influence coefficient method of determining the locations of unbalances on a flexible rotor system and the correction weights. A computer software for calculating the at-the-site balancing of a flexible rotor system was created using C++ language at the Hanoi University of Technology. This software can be used by balancing flexible rotors in Vietnam.